LEGAL ANALYSIS OF THE CRIME OF TRAFFICKING IN PERSONS THROUGH WATERS IN THE PERSPECTIVE OF CRIMINOLOGY (STUDY IN THE WATERS OF BELAWAN): ANALISIS HUKUM TERHADAP TINDAK PIDANA PERDAGANGAN ORANG MELALUI PERAIRAN DALAM PRESPEKTIF KRIMINOLOGI (STUDI DI WILAYAH PERAIRAN BELAWAN) - Dody Ichsan Ramadhan; Rizkan Zulyadi; M. Citra Ramadhan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Belawan waters are waters that directly lead to the waters of the Malacca Strait and are a human trafficking route that is frequently traversed by perpetrators. The existence of cases of human trafficking that occur in the Malacca Strait area will certainly have an impact on the security of the strait. There are three main principles of national security that could be threatened by cross-border cases, namely sovereignty, territorial integrity, political, social, economic and cultural sustainability. This research aims to examine the factors causing human trafficking through Belawan waters from a criminological perspective; to determine the forms of supervision and law enforcement in Indonesian waters in eradicating criminal acts of human trafficking and to examine obstacles to law enforcement of criminal acts of human trafficking through Indonesian waterways. This research method uses normative legal research. The data used is secondary data with primary, secondary and tertiary legal materials as research data sources. The data obtained comes from statutory regulations and developing legal theories related to human trafficking. Data analysis was carried out using qualitative analysis. The results of this research are the first that factors causing human trafficking through Belawan waters include internal factors consisting of economic influence (poverty), negligence of victims, authoritarian societal cultural factors, lack of expertise or skills of victims, low education, lack of job opportunities, lack of access to information and occupational risks. Meanwhile, external factors can be influenced by weak immigration control in a country, lack of coordination between immigration and the police and the Indonesian Navy in the Belawan waters. Second, that the form of supervision and law enforcement in Indonesian territorial waters is to eradicate criminal acts of human trafficking by carrying out penal efforts through law enforcement in accordance with Law Number 21 of 2007 and non-penal efforts by prioritizing preventive efforts. Third, that Obstacles law enforcement of criminal acts of trafficking in persons through Indonesian waterways, including weak supervision by the police and immigration which does not provide information on trafficking in persons; Community indifference in preventing human trafficking cases; The case handling process can take a relatively long time; Development of the Modus Operandi for the Crime of Human Trafficking; There is a condition that the victim does not know that he is being exploited or is a victim of human trafficking; Minimal budget for law enforcement officers.